An Instrument For Assessing Local Enterprise’s Internal Capacity In Linkage With Foreign Direct Investment - HOANG, NGUYEN THANH (The journal of contemporary issues in business and government, 2021)
This paper aims to develop an instrument for assessing the internal capabilities of local enterprises on levels corresponding to their readiness to participate in the global supply chain through linkages with foreign direct investment enterprises. The levels reflect the scope of business activities either in “Local”, “Regional”, “National”, “International” or “Global”. The instrument is built on the resource-based theory, including five major domains in terms of corporate governance capacities, human resources, finance, technology, and supply. Twenty indicators are selected from opinions of local and foreign business managers. Their opinions were reflected in 55 formal articles published in mainstream journals in Vietnam from 2016 to 2019. The reliability and validity of the scale are strictly tested. The results determine that this instrument is suitable to apply to related experimental studies. This is a newly developed tool to assess the internal capacity of domestic firms to link with foreign firms.